ChemInform Abstract: An Efficient One‐Pot Microwave Assisted Synthesis of Dibenzoazepinones. Issue 37 (22nd August 2013) - Deb, Prasant K.; Sharma, Somesh; Borude, Avinash; Singh, Ravi P.; Kumar, Deepak; Reddy, L. Krishnakanth
Abstract The Suzuki coupling of 2‐(2‐bromophenyl)acetic esters with 2‐aminophenyl boronates is found to be optimal in the sequence A) + B) or in the one‐step process C).